The Effects of Feeding Antibiotic on the Intestinal Microbiota of Weanling Pigs - Lourenco, Jeferson M.; Hampton, Rachel S.; Johnson, Hannah M.; Callaway, Todd R.; Rothrock, Michael J.; Azain, Michael J. (Frontiers in Veterinary Science, 2021)
This study investigated the use of carbadox in the diet of nursery pigs. Ten pens of weanling piglets were assigned to 2 treatments: one containing carbadox and another without it. From days 21 to 35 of age, the first group of piglets was fed carbadox at 55 mg/kg of diet; followed by 27.5 mg/kg from days 36 to 49; and 0 mg/kg from days 50 to 63. The second group of pigs was fed a control diet without carbadox from days 21 to 63 of age. On days 35, 49, and 63, fecal samples were collected directly from the rectum of 2 piglets in each pen, and the samples were subjected to microbial DNA sequencing and metagenomic functional analysis using the 16S rRNA gene. Feed conversion from days 21 to 63 was improved (P = 0.04) in the group of piglets fed carbadox. Faith’s phylogenetic diversity was similar (P = 0.89) for both groups of piglets on day 35, but it was diminished (P = 0.01) in the carbadox-fed group on day 49; however, following the complete removal of carbadox from their diets, this microbial diversity index was once again found to be similar (P = 0.27) in both groups on day 63. Likewise, abundances of Slackia, Peptococcus, Catenibacterium, Coprococcus and Blautia were all similar between the two groups (P ≥ 0.40) on day 35, but were smaller in the carbadox group (P ≤ 0.05) on day 49; however, on day 63, abundances of all these genera were once again similar (P ≥ 0.29). Metabolic pathways involved in cellular growth, death, and genetic information processing (translation) were found to be similarly expressed in the microbiota of piglets from both groups on day 35 (P ≥ 0.52), but decreased in the carbadox group on day 49 (P ≤ 0.05), and were similar again in both groups on day 63 (P ≥ 0.51). These results revealed that feeding carbadox to piglets during the first 4 weeks after weaning significantly affected their fecal microbiotas; however, 2 weeks after the removal of carbadox, those changes tended to disappear, indicating that the shifts were carbadox-dependent.